The decriminalisation of abortion in Colombia as cautionary tale. Social movements, numbers and socio-technical struggles in the promotion of health as a right (2019)
This paper discusses the complexity of contemporary struggles for collective health in Colombia, by analysing the efforts of different actors to inscribe abortion as a matter of public health and as a human right. In 2006 the Colombian Constitutional Court (Sentence C 355 of 2006) partially decriminalised abortion in specific circumstances. Such a change in regulation was the result of the strategic coordination of international organisations, researchers and women’s social movements. These groups produced a powerful network of international regulation and epidemiological data about abortion’s mortality and burden of disease in order to move the discussion from the moral field to public health and international law. Despite the significance of the sentence in terms of civil rights, ten years after the regulation there is no clarity about its impact. Conservative sectors within the government have limited the operation of the regulation, through eliciting convoluted rules for hospitals and care providers. On the other hand, data about safe abortions are weak and precarious. Recently groups opposed of abortion have exploited such weakness to undermine the impact of the decriminalisation and to criticise the justification of legalising abortion as a matter of public health. © 2018, © 2018 Informa UK Limited, trading as Taylor and Francis Group.